(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
This article examines the principle of completeness in the context of legal codification, emphasizing its critical role in ensuring a coherent, accessible, and effective legal system. By analyzing historical and contemporary examples, the study highlights how the principle of completeness contributes to the stability and adaptability of codified legal systems.